Distal Finger Reconstruction by Bilateral Lateral Hallux Osteo-onychocutaneous Free Flap. (March 2019) - Wang, Zengtao; Sun, Wenhai; Lineaweaver, William C.; Hao, Liwen; Qiu, Shenqiang; Zhang, Lishan; Chen, Chao; Chiu, Yung-Cheng; Yilihamu, Yilizati; Zhang, Feng
Abstract : Objective: In this report, we present our experience on the use of bilateral lateral hallux osteo-onychocutaneous free flaps for reconstruction of distal finger and the aesthetic and functional results of this technique in a series of cases. Patients and Methods: From February 2005 to May 2015, 7 patients underwent finger reconstruction distal to the distal interphalangeal joint using the bilateral lateral hallux osteo-onychocutaneous free flaps. The mean age was 29.3 years (range, 24–33 years). The lateral hallux osteo-onychocutaneous flaps were harvested from bilateral donor sites. The size of each flap was designed based on the size of half distal finger defect. The lateral hallux osteo-onychocutaneous free flaps from both donor sites were combined to reconstruct the distal finger. More than 50% of hallux nail was preserved in each of donor sites, which was covered with a local flap. Results: All flaps used for reconstruction survived without complications after surgery. The average length of follow-up was 93.4 months (range, 16–163 months). All reconstructed distal fingers showed good aesthetic appearance, except one that underwent a secondary debulking procedure. The average total active motion of the finger was 215.7 degrees (range, 200–230 degrees). Neither pain nor numbness sensation in the reconstructed fingers was complained by the patients. The donor site morbidity was minimal. All patients had pain-free and good function outcome in both feet. Conclusions: The use of the bilateral lateral hallux osteo-onychocutaneous free flaps may provide an option for distal finger reconstruction with satisfactory function and anesthetic outcomes with minimal hallux donor site morbidity.